IMPROVEMENT OF POSTURAL FUNCTION OF THE LOWER EXTREMITY AFTER TOTAL HIP REPLACEMENT - David Kanche; Gergana Nenova; Mina Ivelinova; Daniela Popova (Journal of IMAB, 2023)
Postural control is an integral part of the human motor function in a state of health and illness. Postural control impairments are often found in injuries and diseases of the musculoskeletal and nervous systems. Degenerative processes in the hip joint adversely alter the mechanoreception, which problem can be eliminated through total hip replacement. The purpose of this study is to follow the static balance recovery process, following a total hip replacement, after a 30-day sensorimotor stimulation at home. Material and methods: Material: the study involves 20 women (60-72 years old) who underwent total hip replacement and a following sensorimotor stimulation at home. Methods: pain rating, according to the Visual Analogue Scale (VAS); Manual Muscle Testing (MMT) of certain muscle groups; test for static and dynamic balance, and postural control Results: The obtained results show a significant improvement in motor and postural function during the postoperative period due to systematic physiotherapy at home. Conclusions: the approved sensorimotor training program is easily implemented individually and at home and can be successfully integrated with other physiotherapeutic means from the functional recovery programs for total hip replacement during the minimally protective phase or chronic recovery period.